Developing the Preterm Breastfeeding Attitudes Instrument: A tool for describing attitudes to breastfeeding among health care professionals in neonatal intensive care. (March 2021) - Gerhardsson, Emma; Oras, Paola; Mattsson, Elisabet; Blomqvist, Ylva Thernström; Funkquist, Eva-Lotta; Rosenblad, Andreas
Highlights: The instrument can identify professionals' attitudes before and after breastfeeding education. The attitudes: Facilitating, regulating and Breastfeeding- and skin-to-skin contact friendly. Positive correlation between years health care professionals had worked and their attitude scores. Health care professionals who had previously received breastfeeding education scored higher. Abstract: Objective: The aim of this study was to develop an instrument that measures health care professionals' (HCPs) attitudes to breastfeeding and skin-to-skin contact in relation to the Baby-Friendly Hospital Initiative for neonatal intensive care. Design: The study was part of a larger project aiming to revive the Ten Steps to Successful Breastfeeding for both full-term and preterm infants. The study had a pre-test/post-test design using online questionnaires distributed by email before and after a training programme. Setting and participants: A total of 70 specialist registered nurses, registered nurses, assistant nurses and physicians working at a Swedish neonatal intensive care unit answered 55 breastfeeding attitudes questions online before the training. The Preterm Breastfeeding Attitudes Instrument (PreBAI) consists of twelve of these 55 items/questions, selected using exploratory factor analysis. Measurements and findings: Higher scores indicated more positive attitudes and the median total PreBAI score was 42 points (out of 48), on both the pre- and the post-test questionnaires, showing no significant difference. In the pre-test questionnaire, the majority of HCPs (84%) stated that they needed further breastfeeding training. They also stated that they perceived breastfeeding as very important, scoring a median of 10 (range 5-10) points on a 10-point scale. Three separate underlying dimensions were identified in the questionnaire, indicating different attitudes: Facilitating (five items), Regulating (four items), and Breastfeeding- and skin-to-skin contact-friendly (three items). A positive correlation was found between how many years the HCPs had worked in neonatal care, and their PreBAI score (rs = 0.383, p = 0.001). Those who had previously received extra breastfeeding education scored higher on the instrument. Key conclusions and implications for practice: Neonatal intensive care units need to increase their efforts to support breastfeeding. An important factor for mothers when establishing breastfeeding is support from well-trained professionals with a positive attitude to breastfeeding. The PreBAI could be a useful tool for identifying attitudes among HCPs before and after attending a breastfeeding training programme.